2014
DOI: 10.1146/annurev-fluid-011212-140616
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamics of Heavy Vehicles

Abstract: We present an overview of the aerodynamics of heavy vehicles, such as tractor-trailers, high-speed trains, and buses. We introduce three-dimensional flow structures around simplified model vehicles and heavy vehicles and discuss the flow-control devices used for drag reduction. Finally, we suggest important unsteady flow structures to investigate for the enhancement of aerodynamic performance and future directions for experimental and numerical approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(78 citation statements)
references
References 113 publications
0
76
0
2
Order By: Relevance
“…The second term includes a longitudinal velocity deficit contribution, a vortexinduced drag contribution and a Reynolds stress contribution. The last term represents the rate of change 2 ) comprises only velocity fluctuations, but due to the quadratic nature of its components has both a mean and fluctuating part. Reducing the size of this term reduces D. That is, reducing velocity fluctuations normal to the streamwise direction, or increasing velocity fluctuations in the streamwise direction, results in a time-averaged drag reduction.…”
Section: The Relationship Between Mean Drag and Flow Fluctuationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second term includes a longitudinal velocity deficit contribution, a vortexinduced drag contribution and a Reynolds stress contribution. The last term represents the rate of change 2 ) comprises only velocity fluctuations, but due to the quadratic nature of its components has both a mean and fluctuating part. Reducing the size of this term reduces D. That is, reducing velocity fluctuations normal to the streamwise direction, or increasing velocity fluctuations in the streamwise direction, results in a time-averaged drag reduction.…”
Section: The Relationship Between Mean Drag and Flow Fluctuationsmentioning
confidence: 99%
“…The issue of how to best capture the (v (t) 2 2 ) term using body-mounted pressure sensing is an open question. Reducing the above bracketed term reduces the mean drag, D, and also tends to reduce drag fluctuations, D (t).…”
Section: Linear Feedback Control For Fluctuation Attenuationmentioning
confidence: 99%
“…Passive control has been widely applied on bluff bodies. The use of base cavities and boat tails is considered to be one of the most effective devices for base drag reduction (Choi et al 2014). Such passive approaches, however, are restricted by design and practical considerations and cannot be 'turned off' when not needed.…”
Section: Introductionmentioning
confidence: 99%
“…At motorway speeds, aerodynamic drag arising from vortex shedding over the bluff rear end of the vehicle is responsible for up to two thirds of this energy consumption [2,3]. Initial numerical studies of prototype bluff body flows have shown the potential for feedback control to suppress vortex shedding, thus leading to an overall increase in base mean pressure.…”
Section: Introductionmentioning
confidence: 99%